A JUVENILE LARIOSAURUS (REPTILIA, SAUROPTERYGIA) FROM THE KALKSCHIEFERZONE (UPPERMOST LADINIAN) NEAR VIGGIU' (VARESE, NORTHERN ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1993)
The collection of a juvenile Lariosaurus specimen in the Kalkschieferzone of Cà del Frate (Viggiù, Varese, Northern ltaly), allows the comparison with an other specimen of about the same size, collected from the same formation in the locality of Val Mara (Switzerland) and described as a new species: L. lavizzarii (Kuhn-Schnyder, 1987). The analysis of the size and proportions of both specimens testifies that the supposed difference of relative proportions between the anterior and posterior stylopodium with other known Lariosaurus specimens is due to an error in the calculation or in the plotting of the data, while allometric growth of both anterior and posterior stylopodium is confirmed. A large specimen was already collected from the same formation in the Italian locality of Cà del Frate, and it was ascribed to a separate species, L. valceresii Tintori & Renesto, 1990, on the basis of the relatively longer humerus with respect to L. balsami. This character, however, is not recognizable in the juvenile Lariosaurus specimen from the same locality. Two alternative conclusions are proposed: the small specimen belongs to the same species of the larger one, but the early growth stage obscures the main diagnostic character, or the different limb proportions in the large individual reflect sexual dimorphism rather than specific diversity.
Keywords: Lariosaurus (Reptilia; Sauropterygia); Kalkschieferzone (uppermost Ladinian); Systematic discussion.